Analyses of Base of the Development and Organize of the Digital Television Format - Rayimdjanova Odinakhon Sadikovna; Usmonali Umarovich Iskandarov; Orifjonova Mohidil Oqiljon qizi (Genius Journals, 2023)
The article analyzes the basics of development and formation of the digital television format, the theoretical basis of DVB-T2 (digital video broadcasting) digital television standard programs, signal transmission scheme and comparison tables of channels.
Keywords: digital television; modulation; broadcast; protocol